Influence of cyclical water stress and duration on growth, physio-biochemical and leaf anatomy of mas cotek (Ficus deltoidea Jack) - Raship, Izyani (2018)
Mas Cotek (Ficus deltoidea) is a local herb species that has recently gained commercial importance due to its usage in herbal medicine. It has been used as a tonic for women’s health, rejuvenation and treatments of pneumonia, migraine, stroke, dysentery, hypertension, diabetes and for improving blood circulation. Currently, commercialization of Mas Cotek as ingredient in bottled drinks, herbal medicines capsules, sachets of tea or coffee and oil, has led to increase in market demand for this species. With increasing consumer demand, efforts must be initiated to increase the supply of raw materials and concomitantly reduces exploitation of the species from its native habitats. Information on the response between the levels of biochemical compounds, growth and leaf anatomical changes with water stress is still lacking for Mas Cotek. All experiments were conducted under a shaded rain-sheltered facility at the Malaysian Agricultural Research Institute (MARDI) Research Station, Serdang. Plant materials of MFD 4 accession, propagated from stem cuttings, were used. In the first experiment, study was undertaken to examine the influence of duration and cyclical water stress on growth, dry matter yield and partitioning; and biochemical compounds of Mas Cotek. The study was carried out using a Randomized Completed Block Design (RCBD) with a 4 x 3 factorial arrangements of four cyclical water stress [cyclical water stress were achieved by withholding irrigation at 0 (well watered), 7, 14, and 21 days intervals] and three durations of the stress imposition (60, 120 and 180 days after treatment) with 6 replications. The effects on growth, dry matter production and partitioning, growth analysis, biochemical compounds and leaf physiological characteristics of Mas Cotek were recorded. Results from the experiments showed that growth of plants were affected significantly by the cyclical water stress treatment. Water stress significantly reduced all growth parameters with higher reductions in longer duration of stress. Data showed that the responses to cyclic water stress was significantly decreased and biochemical compound (vitexin, isovitexin and total phenolic content) were significantly affected by water stress. Seven days CWS can be considered as a best option for manipulation to induce higher production of bioactive compounds of Mas Cotek base on the duration of stress imposition. In the second experiment conducted, the responses on physiological processes and leaf anatomy of Mas Cotek imposed with different water regimes (well water and water stressed) were investigated. Cyclic water stress resulted in significant decrease in photosynthesis rate, stomatal conductance, transpiration rate and water use efficiency as compared to the well watered treatment. Chlorophyll a, chlorophyll b, total chlorophyll content, SPAD relative chlorophyll content, relative water content, chlorophyll fluorescence and leaf tissues were not significantly affected by water stress except for spongy cells. In conclusion, Mas Cotek plants are not sensitive to short term water stress and able to cope with mild water stress conditions.